WORKPLACE BULLYING DENGAN SELF-ESTEEM PADA KARYAWAN DI PERUSAHAAN KAYU - Sealien Rampengan Swarah; Sutarto Wijono (Program Studi S1 Psikologi, 2020)
This study aims to determine the correlation between workplace bullying with self-esteem. The research method that I use is quantitative method. The population of respondents was 148 employees. The research sample was taken from the total population (saturation sample) of 121 employees. The self-esteem scale is using from the Organization based on Self-esteem (OBSE) by Pierce (1989), and the workplace bullying is from the Negative Acts Questionnaire Revised (NAQ-R) by Einarsen (2009). Data analysis using Spearman rho technique with SPSS version 25. The results showed that there iss no correlation between workplace bullying and self-esteem (r = -0,168; P> 0.05). Meanwhile, the t-test results showed that there are significant differences in self-esteem based on gender.